2019
DOI: 10.1055/s-0038-1676814
|View full text |Cite
|
Sign up to set email alerts
|

Limitations in the Assessment of Prosthesis-Patient Mismatch

Abstract: Background Prosthesis-patient mismatch (PPM) after aortic valve replacement (AVR) may affect survival but data are conflicting. It is assessed by relating effective orifice area (EOA) to body surface area (EOAi). EOA is patient-specific as the result of flow-velocity times area at the individual patient's outflow tract levels (LVOTA) divided by trans-prosthetic flow velocity. However, some studies use projected EOAs (i.e., valve size associated EOAs from other patient populations) to assess how PPM affects out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Recently, the value of indexing EOA for PPM measurement has been discussed and re-evaluated, as it relates a measure of flow velocity to individual parameters two times (i.e., left ventricular outflow tract [LVOT] area and BSA) ( 13 ). In addition, based on a series of studies having measured Bernoulli's pressure gradients and patient-specific EOAs, Amorim et al identified a significant correlation of transprosthetic pressure gradients to EOA.…”
Section: Ppm Measurement and Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the value of indexing EOA for PPM measurement has been discussed and re-evaluated, as it relates a measure of flow velocity to individual parameters two times (i.e., left ventricular outflow tract [LVOT] area and BSA) ( 13 ). In addition, based on a series of studies having measured Bernoulli's pressure gradients and patient-specific EOAs, Amorim et al identified a significant correlation of transprosthetic pressure gradients to EOA.…”
Section: Ppm Measurement and Definitionmentioning
confidence: 99%
“…In particular, a low-flow state might result in a pseudo-severe PPM. In addition, depending on the aortic root anatomy, the echocardiographic cross-sectional transprosthetic jet area may differ more or less from the real area available for blood flow ( 13 ).…”
Section: Echocardiographic Assessment Of Ppm After Tavi and Savrmentioning
confidence: 99%
“…This risk can easily be avoided by using pledgeted sutures, although some surgeons may argue that in small aortic annuli, the placement of pledgets into the outflow tract may limit hemodynamic performance. 16 Supraannular placement of an aortic valve prosthesis has been described as a risk factor for PVL. 12,13 This may at first be surprising because a properly placed supra-annular prosthesis should be pushed onto the annulus during diastole, a mechanism which counteracts the development of PVL.…”
Section: Technical Considerations To Avoid Pvlmentioning
confidence: 99%
“…It should be clear that using upledgeted sutures (mainly for the aortic position) and running sutures may carry a greater risk of cutting through potentially friable tissue. This risk can easily be avoided by using pledgeted sutures, although some surgeons may argue that in small aortic annuli, the placement of pledgets into the outflow tract may limit hemodynamic performance 16 . Supraannular placement of an aortic valve prosthesis has been described as a risk factor for PVL 12,13 .…”
Section: Technical Considerations To Avoid Pvlmentioning
confidence: 99%
“…Thus, it is patient-specific and the same prosthesis in 2 anatomically different patients will result in 2 different EAOs despite the same GOA of the prostheses. 2,3 What is referred to in the text as reference values for EAOs of SHV can therefore only be the mean of all individually measured EOAs after aortic valve replacement. The value thereby reflects the average hemodynamic result of what we do daily.…”
Section: Effective Orifice Area Is Patient-specific! To the Editormentioning
confidence: 99%